The Physical and Chemical Properties of Virgin Coconut Oil (VCO) Product Obtained Through Fermentation and Enzymatic - Prayitno, Sutrisno Adi (Universitas Dr Soetomo, 2019)
Virgin Coconut Oil (VCO) is an oil product derived from coconut without experiencing high-temperature processes and chemical adding. The making of VCO can be done by various methods. One of them is using an enzymatic method that can be combined with fermentation techniques. The purpose of this study was to identify the physical character and chemical properties of the product from a combination of fermentation and enzymatic by using the bromelain enzyme derived from pineapples extract. The fermentation is carried out for 20 hours. The results showed that pineapples extract showed that bromelain enzyme showed by the colour change of pineapples extract to be brown and there were black sediment, the pH average of pineapples extract was 3.6, the highest VCO in the additional treatment was 50% pineapples extract to 70 ml and the lowest at pineapples extract 20% by 52 ml. The general, the flavour and colour are neutral, there was still the distinctive of pineapples. The highest moisture content in VCO oil is 0.36% in addition to pineapples extract 40% and the lowest is 0.14% from the addition of 30% pineapples extract. While the highest FFA level was at the addition of 20% pineapples extract concentration with FFA value of 0.36%, while the addition of 50% pineapples extract which produced FFA content was 0.32%. The results of the study concluded that the VCO produced was good, but the physical characteristics of the aroma did not meet the requirements.